The effect of gender and code of~ethics on budgetary slack ethical~judgment: Experimental evidence from Indonesia - Jurica Lucyanda; Mahfud Sholihin (Journal of Economics, Finance and Administrative Science, 2023)
Purpose - This research aims to study budgetary slack from a behavioural perspective, especially examining the effect of gender and code of ethics on budgetary slack ethical judgment. Design/methodology/approach This study adopts the experimental method of 2 3 between-subjects mixed factorial design with 102 participants to test the hypotheses. The participants are undergraduate and postgraduate accounting students at a major university in Indonesia. Findings The results show that gender affects budgetary slack ethical judgment, in which women judge budgetary slack as more unethical than men. Additionally, the results indicate that individuals consider budgetary slack more unethical when a code of ethics is present than when it is absent. Originality/value This study contributes to the management accounting literature and behavioural research by understanding budgetary slack from an ethical perspective. Additionally, this study contributes to ethics literature by identifying the effect of gender and code of ethics on budgetary slack righteous judgment.
Keywords: A22; A23; C90; D91; M41; 330; Behavioural research; Budgetary slack ethical judgment; Code of ethics; Experiment; Gender; Mixed factorial design